1976
DOI: 10.1111/j.1440-1819.1976.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Abnormalities in Epileptic Patients Treated with Diphenylhydantoin

Abstract: Summary An immunologic study was made on 170 epileptic patients treated with antiepileptic drugs. The most noteworthy finding was that the serum IgA was decreased in 22 patients, and an IgA deficiency noticed in 12 of them. The blastic transformation rate of lymphocytes in PHA‐containing cultures appeared low in seven out of 12 patients. Other findings included decreased serum IgM and IgG in some patients. These abnormalities were not encountered in epileptic patients taking no anti‐epileptic drugs. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…However, there is suggestive evidence that smoking (89) and alcohol consumption (90) can impair some functions of immunity. Beyond that, many experiences like pregnancy and anesthesia (91), for example, and a wide range of drugs including chlorpromazine (92), diphenylhydantoin (93), and some antibiotics (94) may temporarily depress cellular immunity. The list of substances and circumstances which can produce immunosuppression is impressive as even a rapid perusal of the Index Medicus can attest.…”
Section: Methodologic Issuesmentioning
confidence: 99%
“…However, there is suggestive evidence that smoking (89) and alcohol consumption (90) can impair some functions of immunity. Beyond that, many experiences like pregnancy and anesthesia (91), for example, and a wide range of drugs including chlorpromazine (92), diphenylhydantoin (93), and some antibiotics (94) may temporarily depress cellular immunity. The list of substances and circumstances which can produce immunosuppression is impressive as even a rapid perusal of the Index Medicus can attest.…”
Section: Methodologic Issuesmentioning
confidence: 99%
“…Patients taking antiepileptic drugs have often lower concentrations of IgA in saliva than healthy individuals (Aarli, 1976~;Kanoh and Uchino, 1976;Yabuki and Nakaya, 1976). This finding is observed more often in children and young adults than in adults (Aarli, 1976~).…”
Section: Iga Deficiency: Does It Have Clinical Consequences?mentioning
confidence: 99%
“…Yabuki and Nakaya [32] observed that a significant number of patients, had slightly low serum IgM level among epileptic patients on oral antiepileptic drugs. Conversely, there were also many patients, who had high IgG levels above the normal range.…”
Section: Antigen Specific Tolerance To Unknown Auto Antigensmentioning
confidence: 98%